2022
DOI: 10.3390/jrfm15090378
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Spillover Effects during Pre-and-Post COVID-19 Outbreak on Indian Market from the USA, China, Japan, Germany, and Australia

Abstract: We examined volatility spillover effects from five prominent global stock markets to India’s stock market during the pre-and-post COVID-19 outbreak using daily adjusted closing prices between January 2019 and September 2021 from six capital markets. The structural breakpoint was identified as 23 March 2020, as per the breakpoint unit root test, to examine and compare the results pre-and-post COVID-19. Results show that previous period news and volatility feeds the next period’s volatility significantly and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Market volatilities were found to be more sensitive to pandemic news than economic or business indicators (Baek, Mohanty & Glambosky 2020). Thangamuthu, Maheswari, and Naik (2022) examined the volatility spillover on Indian stock markets from other developed markets like the United States, Japan, China, Germany, and Australia and found persistent spillover in the post-pandemic period. Yet the direct spillover effect of COVID-19 on the national stock market or sectoral indices has not been examined in the Indian scenario.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Market volatilities were found to be more sensitive to pandemic news than economic or business indicators (Baek, Mohanty & Glambosky 2020). Thangamuthu, Maheswari, and Naik (2022) examined the volatility spillover on Indian stock markets from other developed markets like the United States, Japan, China, Germany, and Australia and found persistent spillover in the post-pandemic period. Yet the direct spillover effect of COVID-19 on the national stock market or sectoral indices has not been examined in the Indian scenario.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There has been persistent volatility spillover from other global stock markets in Indian markets throughout the post-pandemic period (Thangamuthu, Maheswari & Naik, 2022). However, research on the spillover of COVID-19 cases in the Indian stock markets and, in particular, the sectors that are expected to benefit from the pandemic has not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted over the past three years addresses a significant gap in economic literature regarding the virus's impact on economies. Various approaches have been employed by researchers to measure volatility amidst the COVID-19 outbreak, including breakpoint investigation (Chahuán-Jiménez et al, 2021;Thangamuthu et al, 2022), assessments of stock market information efficiency levels (Chipunza et al, 2020;Arashi & Rounaghi, 2022), and evaluations of contagion effects (Joseph et al, 2020;Samitas et al, 2022), among others. While notable progress has been achieved, precise determinations regarding the direction, magnitude, and transmission pathways remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In extreme situations such as this, the volatility spillover effect within global stock markets becomes significantly intensified. Thangamuthu et al (2022) showed how volatility spread from major economies like the U.S., China, Japan, and others to the Indian market. Similarly, in an analysis of multiple markets, studies observed heightened spillover effects among markets during COVID-19 compared to prior periods (Hassan and Riveros Gavilanes 2021;Balcilar et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in an analysis of multiple markets, studies observed heightened spillover effects among markets during COVID-19 compared to prior periods (Hassan and Riveros Gavilanes 2021;Balcilar et al 2023). Therefore, being able to accurately gauge the spillover effects across varying conditions is essential for understanding the characteristics of global stock market risk transmission, identifying the focus of risk prevention, and is of great practical significance for countries to take targeted measures to prevent imported risks and maintain financial stability (Bae and Karolyi 1994;Thangamuthu et al 2022).…”
Section: Introductionmentioning
confidence: 99%